Quantifying the benefits from a care coordination program for tracheostomy placement in neonates. (July 2020) - Caloway, Christen; Yamasaki, Alisa; Callans, Kevin M.; Shah, Mahek; Kaplan, Robert S.; Hartnick, Christopher
Abstract: Objective: Value-based care models are becoming instrumental in structuring clinical care delivery in our healthcare climate. Our objective was to determine the value associated with implementation of a Family-Centered Care Coordination (FCCC) program for neonates undergoing tracheostomy. Methods: A multi-disciplinary FCCC program was implemented at the Massachusetts Eye and Ear Infirmary and MassGeneral Hospital for Children in January 2013. This program is designed to ensure a safe transition out of the hospital for children undergoing tracheostomy, reduce re-admission rates, and increase caregiver quality of life (QOL). Study participants included neonates undergoing tracheostomy in 2012 and 2015. This retrospective cohort study examined length of stay (LOS), utilized time-driven activity-based costing to estimate the cost of care, assessed caregiver QOL with 1-month Pediatric Tracheostomy Health Status Instrument (PTHSI) scores, and assessed complications with 6-month Medical Complications Associated with Pediatric Tracheostomy (MCAT) scores. Results: Following implementation of the FCCC program, average LOS decreased from 30.5 days (range 17–39) to 16.6 days (range 9–23). The largest process improvement (cost reduction of 61%) occurred in the discharge-planning phase. The overall cost per care cycle was reduced by 36%. A large clinically meaningful benefit was demonstrated for PTHSI (effect size 0.80) as well as MCAT scores (effect size 9.35). Conclusions: We demonstrated the higher outcomes, including reductions in caregiver burden and complication rates, and the lower costs associated with implementation of the FCCC program for neonates undergoing tracheostomy.